Comparative potential of black tea leaves waste to granular activated carbon in adsorption of endocrine disrupting compounds from aqueous solution - A.O. Ifelebuegu; J. E. Ukpebor; C. C. Obidiegwu; B. C. Kwofi (Global Journal of Environmental Science and Management)
The adsorption properties and mechanics of selected endocrine disrupting compounds; 17 β-estradiol, 17 α – ethinylestradiol and bisphenol A on locally available black tea leaves waste and granular activated carbon were investigated. The results obtained indicated that the kinetics of adsorption were pH, adsorbent dose, contact time and temperature dependent with equilibrium being reached at 20 to 40 minutes for tea leaves waste and 40 to 60 minutes for granular activated compound. Maximum adsorption capacities of 3.46, 2.44 and 18.35 mg/g were achieved for tea leaves waste compared to granular activated compound capacities of 4.01, 2.97 and 16.26 mg/g for 17 β- estradiol, 17 α-ethinylestradiol and bisphenol A respectively. Tea leaves waste adsorption followed pseudo-first order kinetics while granular activated compound fitted better to the pseudo-second order kinetic model. The experimental isotherm data for both tea leaves waste and granular activated compound showed a good fit to the Langmuir, Freundlich and Temkin isotherm models with the Langmuir model showing the best fit. The thermodynamic and kinetic data for the adsorption indicated that the adsorption process for tea leaves waste was predominantly by physical adsorption while the granular activated compound adsorption was more chemical in nature. The results have demonstrated the potential of waste tea leaves for the adsorptive removal of endocrine disrupting compounds from water.